2012
DOI: 10.1159/000337983
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Prognosis for Carcinoma of Unknown Origin in Elderly Patients

Abstract: Purpose: Carcinoma of unknown origin has a poor outcome and usually occurs in elderly patients. In this article, we analyzed the prognostic factors in elderly patients with cancer of unknown primary site (CUP) for treatment considerations. Patients and Methods: Patients >70 years old with histologically proven carcinoma were retrospectively reviewed. The prognostic factors were analyzed with univariate and multivariate Cox regression. Results: We included 63 patients aged 70–79 years and 51 patients ≥80 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Several studies have discussed the prognostic factors of CUP in the past decades. Parameters with prognostic value reported in the previous literature include age, sex, smoking history, performance status (PS), histology, site of metastasis, tumor location, number of metastasis, liver metastasis, symptoms, multiple comorbidities, prolonged QT interval, lactate dehydrogenase (LDH), alkaline phosphatase (ALP), albumin (ALB), leukocytosis, lymphopenia, treatment, and socioeconomic factors (3,(19)(20)(21)(22)(23)(24). Our study showed a consistent result of male gender and older age as unfavorable features, and also included these two factors in the final nomogram.…”
Section: Performance Of the Nomogram In Risk Stratificationmentioning
confidence: 99%
“…Several studies have discussed the prognostic factors of CUP in the past decades. Parameters with prognostic value reported in the previous literature include age, sex, smoking history, performance status (PS), histology, site of metastasis, tumor location, number of metastasis, liver metastasis, symptoms, multiple comorbidities, prolonged QT interval, lactate dehydrogenase (LDH), alkaline phosphatase (ALP), albumin (ALB), leukocytosis, lymphopenia, treatment, and socioeconomic factors (3,(19)(20)(21)(22)(23)(24). Our study showed a consistent result of male gender and older age as unfavorable features, and also included these two factors in the final nomogram.…”
Section: Performance Of the Nomogram In Risk Stratificationmentioning
confidence: 99%
“…If only lymph nodes are affected, patients with just the cervical, axillary, and/or inguinal lymph nodes involved have a better prognosis than those with lymph node metastases in pelvic or abdominal locations. Other factors that worsen the prognosis are impaired performance status and previous weight loss [ 55 , 56 ].…”
Section: Targeted Clinical Work-up and Prognosismentioning
confidence: 99%
“…As far as laboratory tests are concerned, common poor prognostic factors are mainly increased lactate dehydrogenase (LDH) and hypoalbuminemia, probably related to weight loss [ 55 , 56 ]. In terms of haematological findings, leucocytosis and anaemia also constitute independent poor prognostic factors [ 57 ].…”
Section: Targeted Clinical Work-up and Prognosismentioning
confidence: 99%
“…They also reported that patients with hypoalbuminaemia (albumin level ≤ 35 g/l) had been associated with significantly worse survival than those with a normal albumin level. Not only for MPM, in the field of malignant disease, SA has been shown as an independent prognostic factor in several cancers [42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%